A tale of two Williams: James, Stern, and the specious present. (3rd May 2020) - Shardlow, Jack
Abstract : As a typical subject, you experience a variety of paradigmatically temporal phenomena. Looking out of the window in the English summer, you can see leaves swaying in the breeze and hear the pitter-patter of raindrops steadily increasing against the window. In discussions of temporal experience, and through reflecting on examples such as those offered, two phenomenological claims are widely – though not unequivocally – accepted: firstly, you perceptually experience motion and change; secondly, while more than a momentary state of affairs is presented in your ongoing perceptual experience, that which is presented nonetheless seems to be of a quite limited temporal extent. These two claims are frequently tied to the notion of the specious present. However, there has recently been a push back against the supposed link between perceived motion and the specious present. I argue that there are two ways of understanding this link, and while one has recently been the target of criticism, the other withstands such criticism. My overarching aim is to clarify the notion of the specious present through a discussion of the notion's origins, in addition to recent criticism directed at the notion, with the hope of reframing how contemporary debates proceed.